Caracterización socio económica y productiva de la parroquia rural ¨San Antonio de Toacaso¨, del cantón Latacunga, provincia de Cotopaxi 2022. - Caiza Clavijo, Michelle Stefany (2022)
This research work was carried out in the rural parish of “San Antonio de Toacaso,” located in the Latacunga canton, Cotopaxi province, bounded on the north by the Pastocalle, and Chaupi parishes, on the south by Saquisilí, Tanicuhí, and Guaytacama, on the east by Tanicuchi and on the west by the Sigchos canton, focused on the socio- economic and productive diagnosis of the parish, promoting direct links from the university to the inhabitants of the sector. The interest was to specify the diagnosis with economic, social and productive indicators that have as a priority the quality of people’s lives in this parish seeking to know the problems that cause the low economy in the population, compiled based on a survey it was possible to verify that the folks do not have the training to cultivate their land and have better economic income.This study aimed to determine the characterizations through a structured survey to collect valuable information on economic, social, and productive indicators. The result shows that the population is active in agriculture and livestock but unfortunately not well paid since its agricultural and milk production are remunerated at the discretion of the intermediaries who close the roads to impede the regular traffic entering to carry the agricultural products.